2019
DOI: 10.5688/ajpe6543
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of the Quality of Pharmacy Education in Brazil

Abstract: Objective. To analyze the quality indicators of pharmacy schools in Brazil comparing public and private institutions. Conclusions.The analysis of the indicators shows an increase in the number of schools in the private sector and a better quality of public institutions.Qualitative research should be carried out to complement the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…Still on the subject of pharmacy undergraduate institutions, indicators related to student performance, faculty, and conditions offered for the development of the learning process showed that the quality of public institutions in Brazil is better than that of private institutions [ 41 ]. In contrast, countries like the United States, England, and Australia have accredited institutions that harmonize pharmacy education, providing higher quality and uniformity in higher education [ 42 – 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still on the subject of pharmacy undergraduate institutions, indicators related to student performance, faculty, and conditions offered for the development of the learning process showed that the quality of public institutions in Brazil is better than that of private institutions [ 41 ]. In contrast, countries like the United States, England, and Australia have accredited institutions that harmonize pharmacy education, providing higher quality and uniformity in higher education [ 42 – 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diversos fatores podem estar contribuindo com essa problemática: o crescimento exponencial dos cursos de Farmácia no Brasil, que tem gerado competição pelos locais de estágio [28,29]; a abordagem tradicional, ainda prevalente nos cursos de Farmácia, a qual separa a teoria da prática, transferindo aos preceptores o papel de ensinar os estudantes a aplicar o conhecimento na prática profissional, o que gera sobrecarga a esse profissional [4]; e a carga horária baixa para os estágios em farmácias comunitárias, em relação aos 20% das 4000 horas mínimos exigidos nas DCN, que dificulta aos estudantes assumirem responsabilidades crescentes ao longo do curso nos locais de prática e ao final se tornarem independentes de forma a contribuir com o serviço de modo mais enfático e sistemático.…”
Section: Discussionunclassified
“…35 Additionally, as the data in this study point out, the increase in pharmacy programs in Brazil is strongly influenced by the model practiced by private educational groups, which use the same curriculum for all programs, regardless of regional specificities, which can be detrimental since private HEIs are rated worse than public HEIs in terms of quality. 36 Kheir et al emphasize that, although the expansion of pharmacy programs in forprofit institutions may be favorable, this increase must be controlled in an attempt to ensure the quality of education.…”
Section: -28mentioning
confidence: 99%